Prevalence, Behaviors, and Factors of Over-the-counter Aspirin Use in Hong Kong - Amy S. M. Lam; Janette W. C. Poon; Haven H. W. Lai; Karen K. L. Yiu; Kelvin K. F. Tsoi (Asian Journal of Social Health and Behavior)
Introduction: Aspirin can be used for cardiovascular disease prevention and analgesic use. Prevalence of over-the-counter (OTC) aspirin use remained unknown in Hong Kong. The study aimed to examine the prevalence of OTC aspirin use, participants health literacy level, and factors for OTC aspirin use in Hong Kong. Methods: This cross-sectional survey study was conducted in two phases from August 2021 to March 2024. Participants were recruited through inperson and online questionnaire distribution with convenient and snowball sampling. Health literacy was assessed using 12-item short-form health literacy instrument (HLS-SF12). Factors for OTC aspirin use were determined by multivariate logistic regression. Results: A total number of 1,215 participants were included in the study. The mean age was 63.2, whereas the majority (74.7%) were female. A total of 16.2% of respondents reported OTC aspirin use. The age-standardized prevalence of OTC aspirin use was 17.1% (95% confidence interval 15.1–19.3). The prevalence of OTC aspirin use was higher in participants who were ever prescribed aspirin (age-standardized prevalence 27.3% vs. 11.6%). Most users reported OTC aspirin use for symptomatic relief. Only half of the respondents (50.8%) reported knowledge of aspirin side effects, whereas most respondents (56.9%) obtained information on aspirin from their family members or friends. Higher health literacy level in health promotion was less likely to use OTC aspirin. Conclusion: Given the suboptimal rate of knowledge on medication side effects and major sources of information from family or friends, health literacy should be improved to ensure safe medication use in the Hong Kong population.